The Bone Marrow-Derived Human Mesenchymal Stem Cell: Potential Progenitor of the Endometrial Stromal Fibroblast - Aghajanova, Lusine (Society for the Study of Reproduction, Inc., 2010)
The cellular sources that contribute to the renewal of human endometrium are largely unknown. It has been suggested that endometrial stem cells originate from bone marrow-derived mesenchymal stem cells (MSC), with subsequent development into endometrial stromal fibroblasts (hESF). We hypothesized that if bone marrow-derived MSC contribute to endometrial regeneration and are progenitors of hESF, their treatment with agents known to regulate hESF differentiation could promote their differentiation down the stromal fibroblast lineage. To this end, we treated bone marrow-derived MSC with estradiol and progesterone, bone morphogenetic protein 2 (BMP2), and activators of the protein kinase A (PKA) pathway and investigated specific markers of hESF differentiation (decidualization). Furthermore, we investigated the transcriptome of these cells in response to cAMP and compared this to the transcriptome of hESF decidualized in response to activation of the PKA pathway. The data support the idea that MSC can be differentiated down the hESF pathway, as evidenced by changes in cell shape and common expression of decidual markers and other genes important in hESF differentiation and function, and that bone marrow-derived MSC may be a source of endometrial stem/progenitor cells. In addition, we identified MSC-specific markers that distinguish them from other fibroblasts and, in particular, from hESF, which is of biologic relevance and practical value to the field of endometrial stem cell research.